Determinación de grados días desarrollo en el cultivo de maíz (Zea mays) - Taco Tenorio, Gladys del Consuelo (2017)
The present investigation was carried out in the Salache campus of the Technical University of Cotopaxi, located in the parish Eloy Alfaro, Canton Latacunga, Province of Cotopaxi, its purpose was to determine the GDD of corn, which is the number of grades / day necessary to complete a Certain development process or phenological phase; Calculated by the formula of Salazar and Others. It was done in maize (Zea mays), recorded the maximum and minimum temperatures per day, the thermal units were determined by the average method and the growth (cm) of the maize plants was recorded. The agroclimatic information recorded in the meteorological station of the Technical University of Cotopaxi and the data record of the height of plants allowed us to generate the graph of the corn growth curve as a function of temperature and height (cm), defining the units Accumulated in the different phenological stages of the plant. The following results were obtained: for the emergency stage, 87 thermal units were accumulated with a duration of 10 days, 3.55 cm of growth, 15.7 ° C of average temperature, the development stage accumulated 310 thermal units with a duration Of 65 days, 66.37cm of growth, 15,63 ° C of average temperature and the stage of flowering accumulated 475 thermal units with a duration of 104 days, 133,03cm of growth, 15,22 ° C of average temperature.